Comparative Analysis of Mandarin Chengyu Translations into Indonesian Using DeepSeek and Google Translate - Darmawati, Darmawati; Azizah, Laelah; Nahnu, Asmuliyati (Universitas Negeri Semarang, 2025)
The translation of chengyu is an essential aspect of Mandarin language studies, as these expressions contain figurative meanings and cultural values that cannot always be interpreted literally. However, users in Indonesia often face difficulties in obtaining accurate chengyu translations, especially when relying on automatic translation tools. This study aims to analyze the comparative results of translating 25 Mandarin chengyu using two AI-based translation tools, Deepseek and Google Translate. Employing a descriptive qualitative analysis method, the data were collected from the translation outputs of both tools and compared based on idiomatic accuracy, cultural contextualization, and translation fluency. The findings indicate that Deepseek tends to produce more natural and accurate translations, as it successfully preserves idiomatic meaning and Mandarin cultural context. In contrast, Google Translate more frequently generates literal and lexical translations, causing several chengyu to deviate from their intended figurative meanings. Of the 25 chengyu analyzed, 17 showed similarities in meaning, while 8 displayed differences, with Deepseek demonstrating superiority in terms of semantic accuracy and word choice. This study concludes that Deepseek is more effective for translating Mandarin chengyu into Indonesian, as it provides translations results that better reflect cultural values ada idiomatic nuances.